Pelatihan Diversifikasi Produk Jeruk untuk Peningkatan Nilai Tambah Jeruk Siam di Desa Sidomekar, Kecamatan Semboro, Kabupaten Jember - Aulia Brilliantina; Irene Ratri Andia Sasmita; Arisona Ahmad (PT. Gyandharma Global Media, 2025)
Sidomekar Village, located in Semboro District, Jember Regency, is one of the main centers of Siamese orange production with abundant yield. However, the selling price of fresh oranges tends to fluctuate, making it necessary to diversify products in order to increase added value and expand the market. A community service team consisting of lecturers from Politeknik Negeri Jember, two students, and one field facilitator carried out training on processing orange-based products such as instant orange drink, orange cookies, and orange candy. The methods included counseling, product-making demonstrations, hands-on practice, and evaluation through interviews and observations. The results showed a 35% increase in participants’ knowledge of food diversification techniques and skills in processing orange products. The products developed had a distinctive orange flavor and the potential to become flagship products of the village. This activity is expected to encourage community economic independence and strengthen Sidomekar’s identity as a center of Siamese orange production.